Multilingual Validation of the First French Version of Munich Dysphagia Test—Parkinson's Disease (MDT-PD) in the Luxembourg Parkinson's Study - Simons, Janine A.; Vaillant, Michel; Hipp, Geraldine; Pavelka, Lukas; Stute, Lara; Pauly, Claire; Krüger, Rejko (Frontiers in Neurology, 2019)
Introduction: The Munich Dysphagia Test for Parkinson’s disease (MDT-PD) was initially developed and validated in the German population as a highly sensitive and specific self-reported screening questionnaire to detect early oropharyngeal symptoms and aspiration risk in patients with idiopathic Parkinson’s disease (iPD). In order to make this tool accessible for prevention in the French speaking populations worldwide, we performed the first French translation and provide a linguistic and psychometric validation in the unique multilingual environment of the Luxembourg Parkinson’s Study. Methods: We performed the translation of the MDT-PD into French according to WHO guidelines and subsequently performed the linguistic validation including native speakers. For psychometric validation, 46 patients with parkinsonism from Luxembourg and the Greater Region without severe cognitive impairment were recruited in the frame of the Luxembourg Parkinson’s Study. All patients were fluent in French and German completed the MDT-PD in both languages (3 times in total). Results: Linguistic and psychometric validation of the French MDT-PD was reflected by a high test-retest (10/26 questions with K>0.6 and 10/26 with 0.4<K0.6) and language reliability (12/26 K>0.6 and 8/26 0.4<K0.6), with an internal consistency for the French (Cronbach’s alpha 0.84) and German version (0.87); strong item collinerarity strengthens the internal consistency. No significant differences between MDT-PD score distribution and clinical parameters assessing, for example, disease progression, motor state, or cognition has been observed. Conclusion: Based on a multilingual approach in the Luxembourg Parkinson Study, we validated the translation of the first French MDT-PD as a non-invasive tool for early detection of dysphagia in patients with parkinsonism. The unexpectedly high number of positively screened patients at earlier disease stages indicate options for new prevention strategies in large French speaking populations worldwide. Diagnostic validation using clinical and endoscopic swallowing evaluation will be continued soon.